(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
Lifestyle is a description of a person behaviour or attitude which is shown through how he carries out activities in accordance with his thoughts about himself which ultimately distinguishes his social status. This study aims to determine the effect of pocket money and the social environment partially or simultaneously on lifestyle. In this study, there was a population of college students in DIY. A total of 60 respondents using a questionnaire. Using a purposive sampling technique, meaning that the sampling method is based on certain considerations that are adjusted to the criteria determined by the researcher which is done randomly. The data analysis technique used is descriptive method and multiple regression analysis. The results of this study prove that pocket money has a positive and not significant effect on student lifestyle. While the social environment has a positive and significant effect on lifestyle. Thus when there is an increase in pocket money, it is more rational in choosing a social environment so as not to get carried away with lifestyle patterns.